2016
DOI: 10.1146/annurev-biochem-060815-014935
|View full text |Cite
|
Sign up to set email alerts
|

Macrodomains: Structure, Function, Evolution, and Catalytic Activities

Abstract: Recent developments indicate that macrodomains, an ancient and diverse protein domain family, are key players in the recognition, interpretation, and turnover of ADP-ribose (ADPr) signaling. Crucial to this is the ability of macrodomains to recognize ADPr either directly, in the form of a metabolic derivative, or as a modification covalently bound to proteins. Thus, macrodomains regulate a wide variety of cellular and organismal processes, including DNA damage repair, signal transduction, and immune response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
298
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(307 citation statements)
references
References 151 publications
(243 reference statements)
8
298
0
1
Order By: Relevance
“…3 D ). Our data showed that a major by-product of hydrolytic reaction is ADP-ribose, as seen for other macrodomain hydrolases (12). However, because the catalytic residues found in other macrodomain proteins such as TARG1 are not conserved in SCO6735 (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…3 D ). Our data showed that a major by-product of hydrolytic reaction is ADP-ribose, as seen for other macrodomain hydrolases (12). However, because the catalytic residues found in other macrodomain proteins such as TARG1 are not conserved in SCO6735 (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Two of three macrodomain proteins have predicted functions. The SCO0909 protein of S. coelicolor is a bacterial-type PARG, predicted to remove poly-ADP-ribosylation (6); whereas SCO6450 is a macrodomain protein predicted to remove mono-ADP-ribosylation, it is a homologue of the MacroD proteins, which are present in representatives from all three domains of life (10, 12). We focused our research on the third macrodomain protein, SCO6735.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrodomains are larger (∼130-to 190-amino acid) globular domains that can bind to ("read") an ADP-ribose monomer or the terminal ADP-ribose moiety in a PAR chain (Table 1; Fig. 2A,B; Karras et al 2005;Feijs et al 2013;Rack et al 2016). The PBZs are short modules (∼30 amino acids) with the con-…”
Section: Arbds: Adp-ribose Readersmentioning
confidence: 99%
“…Other ARBDs include (1) the phosphopeptide-binding FHA and BRCT domains, (2) RRMs, and (3) RGGs (also called GAR domains) (Li et al 2013;Teloni and Altmeyer 2016). a See Kalisch et al (2012), Feijs et al (2013), Krietsch et al (2013), Hottiger (2015), Teloni and Altmeyer (2016), and Rack et al (2016) as well as references therein for a more comprehensive listing of ARBDs. 2006), PAR glycohydrolase (PARG) (Slade et al 2011), TARG/C6orf130 (Sharifi et al 2013), MacroD1 and MacroD2 Rosenthal et al 2013), and the NUDIX family of hydrolases (Daniels et al 2015b).…”
Section: Adp-ribose and Par Hydrolases: Erasersmentioning
confidence: 99%